2003
DOI: 10.1071/rd02096
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic activation of rat oocytes and their development (in vitro)

Abstract: The present study was performed to determine suitable methods for parthenogenetic activation and subsequent development of rat oocytes in vitro. In the first series of experiments, the ability of electrical pulses, strontium, ethanol and ionomycin to activate Sprague-Dawley (SD) rat oocytes was examined. The synergistic effect of strontium and cycloheximide or puromycin was also examined in the second series of experiments. In the third series of experiments, the development of F1 hybrid (SD x Dark Agouti) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…To date, parthenogenetic activation of oocytes was performed in most mammals, including mice, goats, cows, monkeys, and human beings (12)(13)(14)(15)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, parthenogenetic activation of oocytes was performed in most mammals, including mice, goats, cows, monkeys, and human beings (12)(13)(14)(15)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…One of the alternative protocols proposed is parthenogenesis, in which embryonic development is initiated without sperm contribution. Parthenogenetic activation mainly was studied in experimental species (12)(13)(14).…”
mentioning
confidence: 99%
“…This specific characteristic may affect the results of the activation treatment in vitro. A recent study indicated that SD rat oocytes ac tiv ated 10 m in or 2 h follo w ing cer vi cal dislocation showed higher blastocyst development than those of the 4 and 6 h groups [22]. Our results using WI rat oocytes in the present study show that although there was no difference in the percentages of activated oocytes with pronuclei, the ability to d e v e l o p t o t h e b l a s t oc y s t s t a g e d e c l i n e d significantly as the culture duration before activation was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes from WI rats were collected 16,18,20,22,24 or 26 h after hCG injection and subjected to parthenogenetic activation by electrical stimulation in combination with 6-DMAP as described above. Activated oocytes were transferred to fertilization medium and c ultur ed for 22-24 h. T hey wer e then transferred to mR1ECM drops and culture was continued.…”
Section: Experimental Designmentioning
confidence: 99%
“…A strontium protocol was adapted from mouse studies and most frequently used. However, we and others (Hayes et al, 2001;Roh et al, 2003) observed embryolysis in Ca 21 free medium and in 10 mM Sr 21 . Subsequent optimizations included decreasing Sr 21 concentration to 5 mM Sr 21 or supplementing of activation medium with 1.7 mM calcium (Mizumoto et al, 2008).…”
Section: Lessons and Perspectives From Cloningmentioning
confidence: 68%